2007
DOI: 10.1007/s11244-007-0289-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effect of addition of CeO x and Li2O on γ-Al2O3 supported copper, silver and gold catalysts in the preferential oxidation of CO

Abstract: In the study described in this paper we deposited gold, silver and copper on c-Al 2 O 3 as nanoparticles (<4 nm) and investigated the behavior of these nanoparticles in the preferential oxidation of CO in presence of H 2 . In addition, the effect of addition of CeO x and/or Li 2 O was investigated. All the three metals show preferential oxidation of CO at low temperatures. The oxides added to Au/c-Al 2 O 3 , Ag/c-Al 2 O 3 and Cu/c-Al 2 O 3 improve the catalytic performance of the gold, silver and copper. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Similar results were obtained for the other analysed samples (images not shown). Other authors also found gold in the reduced state in doped alumina materials, as reported in the literature (Grisel et al 2000(Grisel et al , 2001(Grisel et al , 2002aGrisel and Nieuwenhuys 2001a, b;Gluhoi et al 2003Gluhoi et al , 2004Gluhoi et al , 2005aGluhoi et al , b, 2006aLin et al 2004;Gavril et al 2006;Gluhoi and Nieuwenhuys 2007a, b;Lippits et al 2007Lippits et al , 2008Lippits et al , 2009). …”
Section: X-ray Photoelectron Spectroscopysupporting
confidence: 56%
See 4 more Smart Citations
“…Similar results were obtained for the other analysed samples (images not shown). Other authors also found gold in the reduced state in doped alumina materials, as reported in the literature (Grisel et al 2000(Grisel et al , 2001(Grisel et al , 2002aGrisel and Nieuwenhuys 2001a, b;Gluhoi et al 2003Gluhoi et al , 2004Gluhoi et al , 2005aGluhoi et al , b, 2006aLin et al 2004;Gavril et al 2006;Gluhoi and Nieuwenhuys 2007a, b;Lippits et al 2007Lippits et al , 2008Lippits et al , 2009). …”
Section: X-ray Photoelectron Spectroscopysupporting
confidence: 56%
“…Commercial oxide samples were used from Fluka (CeO 2 ), Sigma Aldrich (Co 2 O 3 , Fe 2 O 3 , La 2 O 3 , and NiO), Riedel-de Haën (CuO), Merck (MgO, MnO 2 ) and Evonik Degussa (ZnO). Doped alumina samples were also obtained by traditional impregnation of Al 2 O 3 with precursor salts (nitrates) of the same metals (supplied by Sigma-Aldrich), followed by calcination (IC) at 350°C, as described in the literature (Grisel et al 2000(Grisel et al , 2001(Grisel et al , 2002aNieuwenhuys 2001a, b, 2007b;Gluhoi et al 2004Gluhoi et al , 2005aGluhoi et al , 2006bLin et al 2004;Lippits et al 2007Lippits et al , 2008Lippits et al , 2009). The metal load (7% wt.)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations